(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
The research was carried out at the Set-marko center for the production of agricultural muchrooms during two growing seasons in the years 2022-2023. It included five treatments: control, adding biochar at concentrations of 1, 2, 3, 4 g/l to the medium of malt agar, in order to study there effect on the mycelium growth of the mother culture,(G0). The experimental implementation followed the randomized complete block design. The results showed that the treatment of adding biochar at a concentration of 2 g/l was superior to the control at the start of mycelium growth, where the diameter of the fungal colony reached 56.52 mm compared with the control 52.25 mm, and in term of the time required for the growth of the fungal colony until it reached a diameter of 50 mm, which amounted to 14.62 days compared to 19.17 mm days for the control. And it gave the highest growth factor 41.72 mm2/day and was classified from medium-growth fungi compared to the remaining treatments and the control, where the growth coefficient was (36.60, 38.06, 38.11, 30.48) mm2/day for treatments (1, 3, 4, control) respectively, which are all had slow growing